Prediction of clinical symptoms of schizophrenia based on COMT methylation marker - Abd. Rahim, Nour El Huda; Rahim, Mohd Nabil Fikri; Ku Zaifah, Norsidah; Mohd Noor, Hanisah; Abdullah, Kartini; A. Talib, Norlelawati (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Introduction: The dopamine hypothesis of schizophrenia is based on the fact that hyper-dopaminergic state is involved in causing psychosis and antipsychotic drugs block the dopamine receptor. COMT regulates the homeostatic levels of neurotransmitter dopamine in the synapses and plays a role in the neurocognitive function. The dysregulation of dopamine in the prefrontal cortex influences the cognitive function and the severity of the psychotic symptoms in schizophrenia. During epigenetic event, methylated COMT gene may cause reduction in its expression and thus contribute to the clinical presentation in schizophrenia. Therefore, the aim of this study was to assess the feasibility of using COMT DNA methylation for prediction of specific psychotic presentations of schizophrenia.